Do Services and Transfers Reach Morocco's Poor? Evidence from Poverty and Spending Maps - van de Walle, Dominique (World Bank, Washington, DC, 2012)
In the absence of household level data on participation in public programs, spending allocations and poverty measures across regions of Morocco are used to infer incidence across poor and non-poor groups and to decompose incidence within rural and urban areas separately, as well as to decompose improvements in enrolment rates across poor and non-poor children by gender. Programs appear to be well targeted to the rural poor but not to the urban poor. Substantial benefits accrue to the urban non-poor, while benefits largely bypass the urban poor. The analysis also uncovers evidence of impressive progress in primary and secondary school enrolments for the poor as well as for poor girls since 1994. However, here too, the gains are concentrated on the rural poor.